2022
DOI: 10.1021/acs.jpcc.2c03117
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Dependent Electrical Double-Layer Capacitances of the Basal Plane Pd(hkl) Electrodes in HClO4

Abstract: Electrical double-layer capacitance (C DL) measurements are among the key experiments in physical electrochemistry aimed to understand the properties of electrified solid/liquid interfaces. C DL serves as a critical parameter for developing physical models of electrochemical interfaces. Palladium (Pd) electrodes are among the most widely used functional materials in many applications, including (electro)­catalysis. In this work, we report on double-layer capacitances of the basal plane Pd(111), Pd(100), and Pd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…Figure shows the dependence of the parameters R S , R ads,CT , R abs,CT , C DL , and C ads on the electrode potential in 0.05 M H 2 SO 4 . Figures and S7 show the solution resistance, R S , is independent of the applied potential and is 130 and 185 Ω in 0.05 M H 2 SO 4 and 0.1 HF, respectively The double layer capacitance, C DL , varies little around 10 ± 2 and 30 ± 5 μF cm –2 for 0.05 M H 2 SO 4 and 0.1 M HF solutions, respectively, in rather good agreement with recent studies on double layer capacitances of Pd(111) electrodes . Consistent with the blank voltammogram result in Figures a and S6a, Figures and S7 show the adsorption capacitance, C ads , increases to 189 μF cm –2 in the (bi)­sulfate/hydrogen adsorption region (0.27 V RHE ) and 215 μF cm –2 in the fluoride/hydrogen adsorption region (0.33 V RHE ), respectively.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Figure shows the dependence of the parameters R S , R ads,CT , R abs,CT , C DL , and C ads on the electrode potential in 0.05 M H 2 SO 4 . Figures and S7 show the solution resistance, R S , is independent of the applied potential and is 130 and 185 Ω in 0.05 M H 2 SO 4 and 0.1 HF, respectively The double layer capacitance, C DL , varies little around 10 ± 2 and 30 ± 5 μF cm –2 for 0.05 M H 2 SO 4 and 0.1 M HF solutions, respectively, in rather good agreement with recent studies on double layer capacitances of Pd(111) electrodes . Consistent with the blank voltammogram result in Figures a and S6a, Figures and S7 show the adsorption capacitance, C ads , increases to 189 μF cm –2 in the (bi)­sulfate/hydrogen adsorption region (0.27 V RHE ) and 215 μF cm –2 in the fluoride/hydrogen adsorption region (0.33 V RHE ), respectively.…”
Section: Resultssupporting
confidence: 88%
“…Figures 6 and S7 show the solution resistance, R S , is independent of the applied potential and is 130 and 185 Ω in 0.05 M H 2 SO 4 and 0.1 HF, respectively The double layer capacitance, C DL , varies little around 10 ± 2 and 30 ± 5 μF cm −2 for 0.05 M H 2 SO 4 and 0.1 M HF solutions, respectively, in rather good agreement with recent studies on double layer capacitances of Pd(111) electrodes. 39 Consistent with the blank voltammogram result in Figures 5a and S6a, Figures 6 and S7 show the adsorption capacitance, C ads , increases to 189 μF cm −2 in the (bi)sulfate/hydrogen adsorption region (0.27 V RHE ) and 215 μF cm −2 in the fluoride/hydrogen adsorption region (0.33 V RHE ), respectively. Figure 6 shows a broad relatively potential independent plateau on the curve of the hydrogen absorption resistance, R abs,CT , and increase of sulfate anion adsorption charge transfer resistance, R ads,CT , with potential, respectively, in the potential region of (bi)sulfate S9c), close to the value of 0.5 corresponding to a diffusion process.…”
Section: ■ Results and Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In other words, one can use GCNs to characterize and quantify the affinity of the surface for electrolyte components. In Figure 3, the C DL, min ′ values extracted from Figure 2A are plotted versus the special parameter explained as follows (see the description for this parameter and its meaning in the SI, Figure S1, and ref 17). Consider that the GCN can be understood as a measure of "nonsaturated electron density" at the surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For instance, it is necessary to maximize the EDL capacitances in supercapacitors or to normalize the electrocatalytic activity for energy conversion and storage devices. 12−16 Among other groups, we have recently reported that model Pt, Pd, Cu, and Au electrodes demonstrate a somewhat counterintuitive dependence of EDL capacitances on the structure of the electrode surface, 17 its chemical nature, and the nature of the alkali metal cations present in the electrolyte. 18,19 For example, we demonstrated that for both Pt(111) and Au(111) in 0.05 M AMClO 4 (AM = Li + , Na + , K + , Rb + , Cs + ), the EDL capacitance depends linearly on the hydration energy of the alkali metal cation, with the higher hydration energies corresponding to the lower EDL capacitances close to the potential of zero charge (PZC).…”
Section: ■ Introductionmentioning
confidence: 99%